Shifting Fiqh Tradition in Zakat Management: Nahdlatul Ulama’s Strategies to Enhance the Social Welfare of Nahdliyin - Emzaed, Ali Murtadho; Syarifuddin, Sadiani; Hakim, Muhammad Lutfi; Ibrahim, Bukhari (Al-Risalah, 2024)
This article aims to analyze the shift in the orientation of Nahdlatul Ulamaâ€™s (NU) fiqh (Islamic jurisprudence) tradition in managing zakat in Indonesia. The shift occurs in the zakat fund management institution through the Lembaga Amil Zakat Nahdlatul Ulama (LAZISNU) and their fiqh understanding of zakat recipients (mustaá¸¥iq). The article also explores the forms of involvement of the NUâ€™s structural and cultural members, known as Nahdliyin, in their efforts to improve social welfare. As an Islamic philanthropy institution, LAZISNU strategically synergizes with social welfare issues for its community. Despite being the most prominent Islamic community organization in Indonesia and globally, most Nahdliyin fall into the lower to middle-income category. The article employs a qualitative research approach with a descriptive-argumentative methodology, utilizing Harry J. Bendaâ€™s theory of change and sustainability as an analytical tool. The findings reveal a shift in the Nahdliyin zakat management fiqh tradition in three aspects: zakat fund collection through LAZISNU, the broadening of the meaning of fiÌ„ sabiÌ„lillaÌ„h (on the path of God), and the differentiation between zakat collectors (â€˜Ämil) and zakat committees. This shift is attributed to changes in the method of NU legal opinion (fatwÄ) determination from the qawlÄ« to the manhaji. To enhance the social welfare of Nahdliyin, NU consistently participates actively through its Islamic philanthropic actions by modernizing zakat management adapted from technological advancements. Â